Twin City Ethnopolitics: Urban Rivalry, Ethnic Radicalism and Assimilation in the Lakehead, 1900-70 - Rasporich, Anthony (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1990)
Urban politics and ethnicity have been intimately linked in the history of the twin cities, Port Arthur and Fort William, later amalgamated into Thunder Bay in 1970. The historic relationship between political and urban development and ethnicity may be seen in three distinct phases: (1) the era of ethnic exclusion and factionalism in the period 1900-30, when ethnic groups settled into "foreign" enclaves, or "quarters," and largely stood apart from mainstream political parties, particularly those groups like the Ukrainians and Finns who were active on the radical left; (2) the two decades of radical protest and emergent ethnopolitcal activism from 1930-50, which saw the flowering of city "boss" rule in Port Arthur under Mayor C. W. Cox (1934-49), and federal Liberal dominance by C. D. Howe and Rev. Dan McIvor; (3) the postwar era (1950-70) of ethnic assimilation and broad ethnic participation at all levels of civic politics, and among all parties at the provincial and federal levels.